Surface hydrogeneration of vanadium dioxide nanobeam to manipulate insulator-to-metal transition using hydrogen plasma. Issue 3 (3rd July 2021) - Kang, Hyunwoo; Ko, Minhwan; Choi, Hyobin; Lee, Wanggon; Singh, Ranveer; Kumar, Mohit; Seo, Hyungtak
ABSTRACT: This report suggests the process of hydrogen doping in vanadium dioxide (VO2 ) nanobeam using hydrogen plasma, and in turn reveals the modification in the structural, chemical, physical, and electrical properties of VO2 nanobeam that are associated with the different doping concentration. All V2 O5 films were grown by spin-coating followed by heat treatment for the fabrication of VO2 nanobeams. Further, the hydrogen is doped using reactive ion etching process and concentration of hydrogen in VO2 is controlled by power and exposure time of ion etching. The hydrogen plasma-treated VO2 nanobeams exhibits an additional triclinic (T) phase in comparison to monoclinic (M1) phase (observed in the pristine) and shows a decrease in the ratio of V 4+ ions and forming V x + ions (2 ≤  x ≤ 3). In addition, the measured work function of the VO2 nanobeams decreases with increasing hydrogen doping concentration. Further, the conductivity shows increasing behavior with increasing power (etching time) for a fixed etching time (power) at room temperature and the insulator-to-metal transition (IMT) temperature was found to be decrease to ~ 306 K. This study demonstrates the fine-tuning of IMT temperature just by controlling the doping concentration of hydrogen on the surface of VO2 nanobeam at 300 K.